Peningkatan Mutu Ipteks Kewirausahaan (IbK) Pada Siswa Kelas XII SMAN 2 Kota Jambi - Rosmiati Rosmiati; Zuhri Saputra Hutabarat (Jurnal Ilmiah Dikdaya, 2019)
Given that IbK must someday be independent and operationally sustainable, then IbK is given access just as non-profits are then given an extra task to be able to become a profit unit by utilizing human resources and facilities owned. In an effort to create independent science and technology-based new entrepreneurs, it is expected that in accordance with their fields of knowledge, the IbK program can be carried out in the form of entrepreneurship training, placing students to carry out internships in established companies / business units / IbIKK in the School and facilitating student entrepreneurship. The training is carried out to provide entrepreneurial knowledge, encourage the growth of motivation for entrepreneurship, improve management understanding (organization, production, finance, and marketing) and make business plans or business feasibility studies. It is unthinkable, children are taught to be employees in the company, but who founded the company if they were not entrepreneurs. Children, teenagers, really need enough time with adults to be able to support, encourage and help them find out who they are, how the world works, and what their role is in society.